Mass spectrometry imaging reveals the spatial distribution of essential lipids in Daphnia magna – potential implications for trophic ecology. Issue 1 (2nd January 2023) - Pilecky, Matthias; Fink, Patrick; Kämmer, Samuel K.; Schott, Matthias; Zehl, Martin; Kainz, Martin J.
ABSTRACT: Lipids and fatty acids are key dietary components for the nutrition of organisms at all trophic levels. They are required to build cellular structures such as cell membranes, serve as energy storage, and take part in signal transduction cascades. For decades, ecological research investigated how dietary fatty acid availability contributes to the fitness of individuals and their populations. The omega-3 polyunsaturated fatty acid eicosapentaenoic acid (EPA) is of particular interest because its dietary availability determines the fitness of many aquatic consumers. Because of the small body size of zooplankton, only bulk tissue fatty acid analysis was previously performed, and thus the tissue-specific importance of EPA for zooplankton remained elusive. We used matrix-assisted laser desorption/ionization–mass spectrometry imaging (MALDI-MSI) to reveal the tissue-specific distribution of functional phospholipids in the herbivorous zooplankton Daphnia magna . We demonstrate several lipid species for heart, egg, gut, gonad, somatic, and neurological tissues of D. magna, including the compound eye as well as the optical and cerebral ganglion. The compound eye revealed a large diversity in lipid species containing EPA, which were also found in other neurological tissues and eggs. Such knowledge of tissue-specific fatty acid requirements is essential to investigate how selective allocation of dietary fatty acids within this key grazer affects processes on a functional and molecular level from the individual to food web scales. This methodological advancement will facilitate investigations on how invertebrate physiology and behaviour adjust to changing environmental conditions and potentially affect food web structures, including the trophic transfer of dietary fatty acids.